Biogeographical homogeneity in the eastern Mediterranean Sea - I: the opisthobranchs (Mollusca: Gastropoda) from Lebanon - CROCETTA, F.; ZIBROWIUS, H.; BITAR, G.; TEMPLADO, J.; OLIVERIO, M. (Mediterranean Marine Science, 2013)
A reviewed knowledge of the opisthobranch species from Lebanon (eastern Mediterranean Sea), based on literature records (scattered throughout various papers published over a period of more than 150 years) and recently collected material (1999-2002 within the CEDRE framework and other samples), is presented, yielding a total number of 35 taxa recorded from the Lebanese shores identified to species level. Special emphasis has mainly been given to the alien species, for which scattered notes are also given. The known opisthobranch biota is composed of 22 native ( 63%), 12 alien ( 34%) and one cryptogenic ( 3%) taxa. Eleven of these (Berthella aurantiaca, B. ocellata, Aplysia fasciata, Felimare picta, Felimida britoi, F. luteorosea, F. purpurea, Phyllidia flava, Dendrodoris grandiflora, D. limbata and Aeolidiella alderi) constitute new records for the Lebanese fauna, whilst the examined material of a further seven species (Elysia grandifolia, Pleurobranchus forskalii, Aplysia dactylomela, Bursatella leachii, Syphonota geographica, Goniobranchus annulatus, Flabellina rubrolineata) anecdotally cited from Lebanon on the basis of the samples here studied, is here first explained. One additional taxon belonging to the genus Haminoea has been identified to genus level only. Despite the searching effort poning the basis of the material analyzed here, data reported clearly suggest that strong investments are still needed for a better understanding of the eastern Mediterranean opisthobranch fauna.